The use of derivatives in the mining sector : a comparative analysis of companies listed in South Africa, Australia and the UK - Greenbaum, Mark Joel (Department of Finance and Tax, 2014)
This study investigates whether significant differences exist between South African, Australian and United Kingdom mining corporations in terms of derivative usage. The study further investigates whether such differences or similarities are due to size differences, specific mining industry sector differences, or are as a result of specific derivatives being more prevalent in a particular region of the world.